Psychosocial Complaints and Life Satisfaction Among Greek University Students: A Pre- and Pandemic-Era Comparison - Magdalini Katsikidou; Aikaterini Arvaniti; Spyridon Plakias; Dafni Ioannidou; Georgia Oikonomidou; Sarantoula Topali; Aikaterini Lemontzeli; Maria Samakouri (COVID)
This study aims to identify and compare the prevalence and risk factors associated with psychosocial and psychological complaints, as well as life and study satisfaction, among Greek undergraduate students before and during the COVID-19 pandemic. Data were collected in two phases: initially, from 2018 to 2019 (pre-COVID), through face-to-face surveys, and later, from October 2020 to June 2021 (COVID period), through online surveys. The study, conducted at Democritus University of Thrace (DUTH) in Greece, utilized a repeated descriptive and comparative cross-sectional design. The sample comprised 540 and 641 undergraduate students during the pre-COVID and COVID period, respectively. The following questionnaires were used: I. A socio-demographic characteristics form, II. Psychosocial Complaints List (PCL), and III. Satisfaction with Life and Studies Scale (SLSS). During the COVID period, there was an increase of 63% in psychosocial complaints (p < 0.001), as indicated by the PCL total, and a 25% decrease in satisfaction with life and studies (p = 0.001), according to the SLSS, compared to the pre-COVID period. Incidences of “suicidal thoughts”, “sexual problems”, and “extreme psychological distress” nearly doubled (61%, 67%, and 104%, respectively) during the pandemic. Females exhibited a 33% increase in the PCL total during the COVID period compared to males (p < 0.001). These findings highlight the profound impact of pandemic-induced changes on students’ mental health and quality of life. Female gender and the pandemic period itself emerged as significant factors influencing these outcomes. Universities should prioritize the development of comprehensive support services to mitigate these adverse effects.